Chlorine and NaCl in hydrous basaltic melts - Rusiecka, MK; Wood, BJ (Elsevier, 2025)
We have determined the solubility and behavior of chlorine in hydrous basaltic melts at high pressures (0.5–1.5 GPa) and temperatures (1200–1300 °C) using the chlorine fugacity control method of Thomas and Wood (2021). By systematically increasing the water content of the melt from 0 to 4 wt% at fixed chlorine and oxygen fugacities we find that addition of H2O leads to an increase in chlorine concentration under all conditions studied. In order to develop a comprehensive equation for chlorine solubility we combined our data with 60 results on anhydrous compositions from Thomas and Wood (2021,2023). We define chloride capacity CCl for each experiment as: 𝐶𝐶𝑙 = (𝐶𝑙 (𝑤𝑡.%))/(√𝑓𝐶𝑙2) × 4√𝑓𝑂2 The 70 results were then fitted by stepwise linear regression to an equation containing pressure, temperature and compositional terms. Terms which did not pass the F-test (α = 0.05) were excluded. This approach led to the following fit-equation, with P in GPa and XSi XCa referring to mole fractions of the oxides on a single cation basis: 𝑙𝑜𝑔𝐶𝐶𝑙 = 1.492 + (4331𝑋𝐶𝑎 ― 3508𝑋𝑆𝑖 + 2440𝑋𝐹𝑒 ― 3921𝑋𝐾 ― 741𝑃)/𝑇 The standard error of the fit is 0.083 and R2 is 0.963. This equation closely approximates that obtained from the results on anhydrous compositions by Thomas and Wood (2023). Surprisingly the term in HO0.5 was found not to be significant, implying that water behaves as an ideal diluent with respect to chlorine. We used our chloride capacity equation to calculate the activity of NaCl in experimentally-produced hydrous basalts of known chlorine content. The method involved combining chloride capacities with Na2SiO3 and SiO2 activities derived from the Rhyolite-MELTS program. The results for NaCl activity were found to be in reasonably good agreement with values obtained from the Thomas and Wood (2023) equation which had been based predominantly on data from silica-rich compositions. Finally, measurements of the compositions of melt inclusions from Etna were used to calculate the activities of NaCl in the inclusions and the salinities of fluids with which the inclusions would be in equilibrium. From the trapping pressures of the inclusions and their compositions we find that decompression from 500 MPa to ∼50 MPa is accompanied, in this case, by a salinity increase from <1 wt% NaCl to ∼50 % NaCl.